2006
DOI: 10.1021/ja062428p
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Basic Ferryls in Cytochromes P450

Abstract: Using a combination of Mössbauer spectroscopy and density functional calculations, we have determined that the ferryl forms of P450(BM3) and P450cam are protonated at physiological pH. Density functional calculations were performed on large active-site models of these enzymes to determine the theoretical Mössbauer parameters for the ferryl and protonated ferryl (Fe(IV)OH) species. These calculations revealed a significant enlargement of the quadrupole splitting parameter upon protonation of the ferryl unit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
105
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 33 publications
13
105
0
1
Order By: Relevance
“…Given the difference in pK a between the phosphate and the substrate (Δ pK a ~ 20) and the short excited-state lifetime of the catalyst (2.3 μs in MeCN at RT [216]), it is unlikely activation proceeds through stepwise PT/ET. Lastly, independent quenching experiments with N-protiated and N-deuterated acetanilide demonstrated a KIE of 1.15; such small KIEs have been demonstrated to be consistent with proton-involvement in multisite PCET processes [46,[217][218][219][220][221] . Taken together, our mechanistic data are most consistent with amide activation proceeding through concerted PCET.…”
Section: Amidesmentioning
confidence: 66%
See 1 more Smart Citation
“…Given the difference in pK a between the phosphate and the substrate (Δ pK a ~ 20) and the short excited-state lifetime of the catalyst (2.3 μs in MeCN at RT [216]), it is unlikely activation proceeds through stepwise PT/ET. Lastly, independent quenching experiments with N-protiated and N-deuterated acetanilide demonstrated a KIE of 1.15; such small KIEs have been demonstrated to be consistent with proton-involvement in multisite PCET processes [46,[217][218][219][220][221] . Taken together, our mechanistic data are most consistent with amide activation proceeding through concerted PCET.…”
Section: Amidesmentioning
confidence: 66%
“…The basicity implies this species is protonated at physiological pH; these authors credit remarkable unusually high basicity to the binding of an axial thiolate ligand. In a later study, Green concluded that the ferryl forms of P540 BM3 and P450 cam were protonated at physiological pH using a combination of Mössbauer spectroscopy and density functional calculations [46]. Where iron-heme complexes such as Horseradish peroxidase C (and its associated Compounds I and II) are poorly oxidizing (approximately 1.08 V at pH = 6.5) [47], these enzymes are among a small set of enzymes capable of cleaving strong C-H bonds [48].…”
Section: Metal-oxo Complexes For C-h Bond Oxidationmentioning
confidence: 99%
“…Recent experimental studies and density functional theory calculations suggest that the ⌬E Q value might correlate with the protonation state of some heme-based ferryl species (62,63). The parameter range for protonated Fe(IV)-OH species is 2.00 -2.5 mm/s (64), whereas the range for unprotonated Fe(IV)ϭO is 1.0 -1.6 mm/s (62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the role of the axial cysteinate ligand of cytochrome P450 has received much attention because of the enzyme's ability to hydroxylate unactivated COH bonds (7)(8)(9)(10). In recent reports, Ogliaro et al (10) and Green and coworkers (11)(12)(13)(14) demonstrated that the thiolate ligand in closely related chloroperoxidase increases the basicity of the iron(IV)-oxo moiety such that the Fe-O unit becomes protonated at neutral pH upon reduction by one electron to the Cpd II state. Green speculated that this increased basicity is a strategy that allows hydrogen atom abstraction by Cpd I to occur at a lower redox potential so that the surrounding enzyme environment can be protected from oxidative destruction.…”
mentioning
confidence: 99%